2008
DOI: 10.1016/j.neuroimage.2008.01.025
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian estimation of synaptic physiology from the spectral responses of neural masses

Abstract: We describe a Bayesian inference scheme for quantifying the active physiology of neuronal ensembles using local field recordings of synaptic potentials. This entails the inversion of a generative neural mass model of steady-state spectral activity. The inversion uses Expectation Maximization (EM) to furnish the posterior probability of key synaptic parameters and the marginal likelihood of the model itself. The neural mass model embeds prior knowledge pertaining to both the anatomical [synaptic] circuitry and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
137
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 123 publications
(139 citation statements)
references
References 58 publications
2
137
0
Order By: Relevance
“…For example, Moran et al (2008) demonstrated that a DCM of steady-state electrophysiological responses correctly inferred changes in synaptic physiology, following a neurochemical manipulation, which were predicted from concurrent microdialysis measurements. In a next step, ongoing rodent studies test whether DCMs can infer selective changes in specific neuronal mechanisms that result from controlled experimental manipulations; e.g.…”
Section: Approximate Probabilistic (Bayesian) Inferencementioning
confidence: 99%
See 1 more Smart Citation
“…For example, Moran et al (2008) demonstrated that a DCM of steady-state electrophysiological responses correctly inferred changes in synaptic physiology, following a neurochemical manipulation, which were predicted from concurrent microdialysis measurements. In a next step, ongoing rodent studies test whether DCMs can infer selective changes in specific neuronal mechanisms that result from controlled experimental manipulations; e.g.…”
Section: Approximate Probabilistic (Bayesian) Inferencementioning
confidence: 99%
“…In these cases it is more efficient to summarize the measured time series in terms of their spectral profile. This is the approach developed by Moran et al (2007Moran et al ( , 2008Moran et al ( , 2009), which models local field potential (LFP) data based on the neural mass model described above, using a linearization of the evolution function f around its steady-state (Moran et al 2007). This approach is valid whenever brain activity can be assumed to consist of small perturbations around steady-state (background) activity.…”
Section: Dcm For Eeg/meg/lfpmentioning
confidence: 99%
“…Bitan et al 2005;Ethofer et al 2006;Fairhall and Ishai 2007;Fan et. al 2007;Grol et al 2007;Mechelli et al 2003;Stephan et al 2007a) and has recently been applied to electromagnetic data as observed with EEG and MEG (Garrido et al, 2007;Kiebel et al, 2007) or invasively recorded local field potentials (Moran et al 2008). Even more recently, we have described a dynamic causal model for spectral responses as summarised by time-frequency representations of source-reconstructed EEG or MEG data (Chen et al 2008).…”
Section: Dynamic Causal Modelling For Induced Responsesmentioning
confidence: 99%
“…The possibility for extracting physiological information on collective network activity from an EEG has been demonstrated [15][16][17][18]. Indeed, collective dynamics in complex systems that consist of interacting subunits can often be captured by a single or few macroscopic observables, which are named the order parameters [22,64,65].…”
Section: Relationship Between Local Eeg Short-term Sp Of Particular Tmentioning
confidence: 99%
“…It was demonstrated that neural activity patterns measurable at the macro-level by EEG are correlated with underlying neural computations [13][14][15][16][17][18]. Thus, EEG provides a direct measure of cortical activity with millisecond temporal resolution.…”
Section: Introductionmentioning
confidence: 99%